Market bidding method for the inter-provincial delivery of cascaded hydroelectric plants in day-ahead markets considering settlement rules - Han, Xu; Shen, Jianjian; Cheng, Chuntian (Frontiers in Energy Research, 2023)
Chinese electricity market reform brings huge challenges to hydropower operations and electricity trading.This study proposes a scheduling method coupling priority electricity and day-ahead trading for large hydropower plants.The study focuses on complex factors such as tariff uncertainty, different types of electricity settlement rules and inter-provincial electricity transmission links.Spot market tariff scenarios were determined through the Latin Hypercube and the K-MEANS methods.A performance formulation of priority electricity deviation considering settlement assessment rules is established. A transmission description for different sub-plants and a triangular linear interpolation method based on binary independent branching mode are proposed to respectively solve inter-regional transmission connections and hydraulic coupling of cascaded hydropower plants. Finally, the big M method is employed to equivalently transform the complex nonlinear problem into a mixed integer linear 2 This is a provisional file, not the final typeset article programming model. The method is verified with the day-ahead operation of four large hydropower plants in the downstream of the Jinsha River in China as a case study. Settlement assessment rules, inter-regional power transmission, and price uncertainty are analyzed in three different cases. Three conclusions are obtained: 1) The priority electricity performance rate and the price are positively correlated, which is useful to guide hydropower plants to actively participate in the market; 2) Introducing the prediction error of electricity price in the model can help to avoid market decision risk and improve the expected return by nearly 1.2%; 3) Considering the settlement penalty rule is helpful for power generation enterprises to improve power allocation and thus seek higher revenue compared to traditional methods without considering it.